The blue room [compact disc] - Peyroux, Madeleine (EmArcy ; Distributed by Universal Music Distribution, 2012)
Georgia-born jazz artist Madeleine Peyroux follows up 2011's Standing on the Rooftop with ten more jazz-inspired songs, including Changing All Those Changes, Guilty, and I Can't Stop Loving You.